Injury of the liver artery in duodenopancreatectomy: . 2 case report - Pérez Zunino, Agustín; Pereyra Cosco, Joaquín; Delgado Galiana, Juan; Carrera Garese, Ximena; Parodi Esteva, Hernán (Cirugía del Uruguay, 2021)
Hepatic artery (HA) lesions during a cephalic duodenopancreatectomy (CDP) cause parenchymal and biliary tree hypoxia, determine necrosis and possible superinfection in a vulnerable liver due to cholestasis, leading to the formation of abscesses and fistulas, increasing the morbidity and mortality of the procedure. We report 2 cases of patients undergoing CDP who presented complications of hepatic ischemic due to accidental lesions of branches of HA.